Penyusunan Buku Pedoman Perkuliahan Konsentrasi Pendidikan Kewarganegaraan - Osa Juarsa; Puspa Djuwita; Abdul Muktadir (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2023)
This manual is presented with the aim that in carrying out practical learning assignments students do not encounter problems that will interfere with the implementation of Civics concentration practical activities in the field. This research is a continuation of the previous year's research. Aims to; (a) producing materials as guidelines for implementing elementary school Civics concentration learning courses, (b) materializing materials as guidelines for Civics concentration lecture activities with contemporary content, (c) availability of adequate practical guidelines for Civics concentration lectures which can be used as a reference for students in lectures, when carrying out field practice assignments, and also in completing final assignments, (d) providing optimal service to basic education master's students. This research was designed using a research and development approach (Research and Development), data collection techniques, namely; interviews, documentation. Analysis uses qualitative data analysis techniques. Analysis was carried out on data on student needs for material content as a practical guide for elementary school Civics lectures. The results of the research are needed and material is really needed as a guide for elementary school Civics lecture activities for students. The implications of the preparation of this book as a practical guide for lectures in the field of elementary school civics can be used as a guide in carrying out each stage of activities during practice in the field. Research conclusions; The Civics concentration lecture manual has been prepared in the form of a book which will be used as a manual, and can be published.